Reduction of pollution levels in the Chatty River through Sustainable Drainage Systems: A case study of the Bethelsdorp River sub-catchment - Matalanga, Anabel (Department of Civil Engineering, 2024)
Chatty River, located in Gqeberha, South Africa, is the largest tributary feeding into the Swartkops Estuary and is among the three significant sources of pollution in the estuary, the other two being the Motherwell Canal and the Markman Canal. The Chatty River Catchment is mainly occupied by low-income residential areas resulting in pollution from stormwater runoff, litter, and raw sewage discharge. There are growing informal settlements and limited agriculture. In recent years, the high pollution level in the Swartkops estuary has led to the reduction and even halting of various social and cultural activities such as the Redhouse River Mile swimming event, cleansing ceremonies by traditional healers, and baptisms by the Zion Church. SuDS are appropriate for a range of contexts and purposes for example to minimise the impact of development on stormwater quality while maximising amenity and biodiversity through a suite of interventions designed to manage stormwater in a way that mimics nature. This study sought to understand the pollution contribution of the Chatty River and provide recommendations to improve its water quality through the possible inclusion of Sustainable Drainage Systems (SuDS). The Chatty River's physical, nutrient, and microbiological characteristics were assessed through water quality sampling and historical data review to identify pollutant hotspots. The high mean dissolved inorganic phosphorus (DIP) concentrations, in the form of orthophosphate, indicate eutrophic and hypertrophic conditions in most sections of the Chatty River. The mean nitrogen concentrations, in the form of dissolved inorganic nitrogen (DIN), on the other hand, were below the eutrophic threshold in most sections of the Chatty River. Microbiological pollutant analysis indicated high gastrointestinal health risks to any residents in the catchment who utilised the water for domestic and recreational use. Overall, no consistent relationship was established between pollutant concentrations and rainfall. This could possibly be because of point pollution for example, from overflowing manholes, which was observed to be intermittent. The extent of pollution highlighted by the water quality sampling indicated the need for mitigation measures. Hydraulic and hydrological models were constructed in PCSWMM, a stormwater management modelling software developed by Computational Hydraulics International (CHI) using the USEPA SWMM model as the ‘engine'. Both the Chatty River Catchment as a whole as well as the Bethelsdorp River sub-catchment, located within the Chatty River Catchment, were modelled to test the potential benefits of SuDS inclusion. Various scenarios were tested including: the current situation (‘As-is'); the likely Pre-Development situation representing the state before the influence of anthropogenic activities; and various retrofitted SuDS interventions. DIN, DIP and total suspended solids (TSS) were the pollutant indicators tracked in the model. DIN and DIP were used to assess the risk of eutrophication. TSS is a good measure of pollution as pollutants such as heavy metals that attach to suspended particles. The SuDS interventions included: a constructed wetland, a retention pond, and various infiltration practices. Six scenarios were explored, including various individual interventions, some regional controls and finally, the combination of all the interventions. Pollutant reduction from the different scenarios ranged from 13-80%. Rehabilitating the wetlands appeared to offer the most significant impact compared to the other regional SuDS interventions in Scenario 1 and 3, with a mean pollutant reduction of 30%. However, a combination of all the interventions had the highest pollutant removal when functioning efficiently of 72% and 80% for DIP and TSS, respectively. This is within the range of treatment required by the City of Cape Town (2009) Management of Urban Stormwater Impacts Policy which was used in the absence of a Gqeberha-specific guideline. Installing a treatment train of multiple SuDS interventions is seen as the most effective strategy to adequately improve water quality in the catchment to meet the standards presented by various guidelines.